Analysis of the Problems in Innovation and Entrepreneurship Education for Business Administration Majors - Ma, Bihong (Journal of Education and Educational Technologies, 2023)
In recent years, China has been vigorously promoting independent entrepreneurship among college students. In order to cultivate more innovative and entrepreneurial talents, a plan combining theory and practice has been proposed to avoid overly written education. This article mainly studies the current situation of innovation and entrepreneurship education in the field of business administration, as well as the focus of teaching and education. Based on a survey of the entrepreneurial situation of business administration students, suggestions are proposed to build a professional oriented innovation and entrepreneurship education model, hoping to better solve the path problem of innovation and entrepreneurship education in the field of business administration.